Plasminogen activator inhibitor-1 and tumour growth, invasion, and metastasis - Durand, Michelle K.V.; Bødker, Julie S.; Christensen, Anni; Dupont, Daniel M.; Hansen, Martin; Jensen, Jan K.; Kjelgaard, Signe; Mathiasen, Lisa; Pedersen, Katrine E.; Skeldal, Sune; Wind, Troels; Andreasen, Peter A. (Thrombosis and Haemostasis, 2004)
In recent decades, evidence has been accumulating showing the important role of urokinase-type plasminogen activator (uPA) in growth, invasion, and metastasis of malignant tumours. The evidence comes from results with animal tumour models and from the observation that a high level of uPA in human tumours is associated with a poor patient prognosis. It therefore initially came as a surprise that a high tumour level of the uPA inhibitor plasminogen activator inhibitor-1 (PAI-1) is also associated with a poor prognosis, the PAI-1 level in fact being one of the most informative biochemical prognostic markers. We review here recent investigations into the possible tumour biological role of PAI-1, performed by animal tumour models, histological examination of human tumours, and new knowledge about the molecular interactions of PAI-1 possibly underlying its tumour biological functions. The exact tumour biological functions of PAI-1 remain uncertain but PAI-1 seems to be multifunctional as PAI-1 is expressed by multiple cell types and has multiple molecular interactions. The potential utilisation of PAI-1 as a target for anti-cancer therapy depends on further mapping of these functions.
Keywords: Proteases; serpins; desmoplasia; angiogenesis